2002
DOI: 10.1080/08873267.2002.9977040
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of consciousness in responses to terrorist attacks: Towards a transpersonal theory of cultural transformation.

Abstract: Through the analyses of responses to attacks to September 11, the authors interpret trauma as a catalyst of transformation of cultural consciousness and American self, and articulate the foundations for a transpersonal theory of cultural evolution. Accounts feature positive values, humanistic and spiritual aspirations, direct intuition of the evolution of consciousness, and the instances of new type of integral consciousness identified with both oneness and multiplicity. Authors use the theory of emergent evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Similarly, in their book entitled Changing European Identities , Breakwell and Lyons (1996) discuss the mechanisms associated with change in identities in the context of the development of the European Union and refer to a loss of national identity. This change in cultural identity is similar to what Wall and Louchakova (2002) describe as a “shift in the cultural collective consciousness” (p.253). This consists of a change in the American self and the emergence of new selves, more independent and alive in the context of change (see also Neves and Caetano, 2009; May, 2011).…”
Section: Constructing a Typology Of Social Change: The Characteristicsupporting
confidence: 71%
See 2 more Smart Citations
“…Similarly, in their book entitled Changing European Identities , Breakwell and Lyons (1996) discuss the mechanisms associated with change in identities in the context of the development of the European Union and refer to a loss of national identity. This change in cultural identity is similar to what Wall and Louchakova (2002) describe as a “shift in the cultural collective consciousness” (p.253). This consists of a change in the American self and the emergence of new selves, more independent and alive in the context of change (see also Neves and Caetano, 2009; May, 2011).…”
Section: Constructing a Typology Of Social Change: The Characteristicsupporting
confidence: 71%
“…They need to adapt to the inconsistent model their societies are projecting, which leads to “socialization ambiguity” (McDade and Worthman, 2004, p. 49). Because social change brings uncertainty in society, it can affect many aspects of individuals' lives such as family relations (Noak et al, 2001), and aspects associated with the self such as “emotions, values, perceptions, identity” (Wall and Louchakova, 2002, p. 266).…”
Section: Constructing a Typology Of Social Change: The Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Levy et al (2002) implied that right after the terrorist attack volunteerism swept the nation and research by Alper (2002) and Wall and Louchakova (2002) reported a cultural transformation had taken place producing more openness with others and a desire for spiritual unity. Brothers (2003) explained that these attitudes and behaviors were attempts by teenagers and adults to reestablish continuity, safety and security into their lives.…”
Section: /11 Impact On Teenage Valuesmentioning
confidence: 99%
“…Dissertation research in transpersonal psychology addresses a wide variety of topics on the boundary between psychology and spirituality, which brings new challenges to phenomenological research methods. Examples of research topics in transpersonal psychology include psychosomatic mysticism (Louchakova & Warner, 2003), spiritual experiences induced by cultural trauma (Wall & Louchakova, 2002), dream yoga (Stefik, 1999), nonordinary states of consciousness in multigenerational family patterns (Little, 2004), science as a path to God (Kuhar, 2004), and the meditative practices of selflessness (Carey, 2004). Focus on spirituality as lived experience aggravates the complexity of phenomenological analysis by several factors.…”
mentioning
confidence: 99%